Analisis Kepailitan PT Istaka Karya Sebagai Badan Usaha Milik Negara - Ledy Wila Yustini; Serlika Aprita; M. Andres Arta Al Fajri (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Overlapping regulations regarding SOE bankruptcy have resulted in inconsistencies in Judges' decisions in deciding SOE bankruptcy cases. The bankruptcy case that befell PT Istaka Karya (Persero) was due to debts in the form of promissory notes that had not been paid. In the Cassation Decision, PT Istaka was declared bankrupt, but in the Judicial Review Decision, PT Istaka's bankruptcy statement was canceled. The writing of this law is intended to find out the legal consequences of canceling a bankruptcy statement at a State-Owned Enterprise (Persero) for paying off its debts to creditors and to find out the reasons for the Supreme Court Review Decision canceling the Cassation Decision in the bankruptcy case of PT. Istaka Karya (Persero). Based on the results of the study, the cancellation of a bankruptcy statement at BUMN (Persero) does not eliminate the obligation of BUMN (Persero) to pay its debts to creditors. Debtor debt problems to creditors after the cancellation of the bankruptcy decision were resolved in a way outside the bankruptcy institution which was agreed upon by both parties. The reasons for the Supreme Court Review decision annulled the Cassation Decision in the bankruptcy case of PT. Istaka is the elimination of the element